2006
DOI: 10.1074/jbc.m601062200
|View full text |Cite
|
Sign up to set email alerts
|

AtIREG2 Encodes a Tonoplast Transport Protein Involved in Iron-dependent Nickel Detoxification in Arabidopsis thaliana Roots

Abstract: Iron acquisition in Arabidopsis depends mainly on AtIRT1, a Fe 2؉ transporter in the plasma membrane of root cells. However, substrate specificity of AtIRT1 is low, leading to an excess accumulation of other transition metals in iron-deficient plants.In the present study we describe AtIREG2 as a nickel transporter at the vacuolar membrane that counterbalances the low substrate specificity of AtIRT1 and possibly other iron transport systems in iron-deficient root cells. showed an increased tolerance to elevated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
202
0
5

Year Published

2009
2009
2020
2020

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 207 publications
(213 citation statements)
references
References 42 publications
6
202
0
5
Order By: Relevance
“…This up-regulation leads to an increase in cytoplasmic iron, but due to the poor substrate specificity of IRT1, it also results in increasing cytoplasmic levels of other toxic divalent metal cations, such as nickel. One of the MAR1 homologs in Arabidopsis, AtIREG2, is proposed to play a role in the vacuolar sequestration of excess nickel accumulated under iron-limiting conditions due to the action of IRT1 (Schaaf et al, 2006). Schaaf et al showed that AtIREG2 was up-regulated under iron deficiency, in contrast to MAR1, which is down-regulated (Fig.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…This up-regulation leads to an increase in cytoplasmic iron, but due to the poor substrate specificity of IRT1, it also results in increasing cytoplasmic levels of other toxic divalent metal cations, such as nickel. One of the MAR1 homologs in Arabidopsis, AtIREG2, is proposed to play a role in the vacuolar sequestration of excess nickel accumulated under iron-limiting conditions due to the action of IRT1 (Schaaf et al, 2006). Schaaf et al showed that AtIREG2 was up-regulated under iron deficiency, in contrast to MAR1, which is down-regulated (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, we suggest that MAR1 and AtIREG2 play distinct roles in the plant cell. Their expression patterns are quite different: AtIREG2 is mainly expressed in the root (Schaaf et al, 2006), while MAR1 is highly expressed in all tissues (Supplemental Fig. S4C).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations